Transparansi Pengelolaan Keuangan Desa Kabupaten Pulau Morotai - Suriana A.R. Mahdi; Rinto Syahdan; Nurdin Nurdin; Irfandi Buamonabot (Society, 2021)
This study aims to provide an overview of the transparency of village financial management in Pulau Morotai Regency, North Maluku Province, Indonesia. The sample in this study was taken by using a purposive sampling method, involving 440 respondents, and spread in 88 villages in Pulau Morotai Regency. Data processing techniques used descriptive statistics with a class interval approach. The results show that the indicators of clarity of roles and responsibilities, implementation of government affairs are still dominated by the head of the village who has the authority for village financial management. Indicators of budget disclosure show relatively the same as indicators of clarity of roles and responsibilities. The indicators of information availability indicate that the accessibility of public information in villages located in the subdistrict capital is relatively good. In contrast, the last indicator, integrity assurance, shows that data validity still being a problem in the village planning process. This study also discusses the implications as well as suggestions for future studies.